Agroecology in action: empowering tribal communities in Mandla, India through trainings on bio-fertilizer and bio-pesticides - Malaiappan, Sudharsan; Goverdhanam, S.; Konwar, D.; Gadewar, P.; Kumar, Gopal; Krishnan, S.; Sikka, Alok (International Water Management Institute, 2024)
This report outlines the training sessions and exposure visits conducted by CGIAR’s Agroecology team in partnership with PRADAN for local communities in Mandla district, Madhya Pradesh, India. Training sessions introduced agroecological practices such as Agroecological Homestead Model (AHM) and Krishi Kund (Microsite) and covered essential topics such as preparation techniques for bio-fertilizer and bio-pesticide preparation, pest identification, and sustainable crop management techniques to 119 farmers (105 females, and 14 males). Additionally, the report outlines the preparation techniques of bio-fertilizers and bio-pesticides such as Neemastra, Kanda Khaad, Jivamrit, Brahmastra, Agniastra, and Mathastra.